Greentech bubbles and investment in a green revolution - Janeway, William (Henry Stewart Talks, 2022)
Green-tech bubble, Investment, Financial speculation, Climate change, Government involvement, Market participation, Technology risk, Market risk, Competition, Digital revolution, Political economics, Evidence-based policy, Faith-based policy, Vision, Fiscal prudence